Preoperative Left Ventricle End Diastolic Volume Index as a Predictor for Low Cardiac Output Syndrome After Surgical Closure of Secundum Atrial Septal Defect With Small-Sized Left Ventricle - Rahmat, Budi; Dwita, Nurima Ulya; Arya Wardana, Putu Wisnu; Lilyasari, Oktavia (Frontiers in Pediatrics, 2021)
Introduction: Low cardiac output syndrome is one of the postoperative complications that is associated with significant morbidity and mortality after surgical closure of atrial septal defect (ASD) with small-sized left ventricle (LV). This study investigated whether preoperative left ventricular end-diastolic volume index (LVEDVi) could accurately predict low cardiac output syndrome (LCOS) after surgical closure of ASD with small-sized LV. Method: This retrospective cohort study involved adult ASD patients with small-sized LV from January 2018 – December 2019 in National Cardiovascular Center Harapan Kita. Preoperative MRI data to assess the left and right ventricle volume were collected. A bivariate analysis using independent student t-test was done. Diagnostic test using receiver operating characteristic (ROC) curve was also done to obtain the area under the curve (AUC) value. The best cut-off point was determined by Youden’s index. Result: Fifty-seven subjects were involved in this study (Age (mean ± SD) 32.56 ± 13.15 years; weight (mean ± SD) 48.82 ±12.15 kg). Subjects who had post-operative LCOS (n=30) have significant lower LVEDVi (45.0 7.42mL/m2 vs 64.1513.37 mL/m2; p<0.001), LVEDV (64.616.0 mL vs 85.920.7 mL; p<0.001), LVSV (38.97  11.5 mL vs 53.13  7.5 mL; p<0.001) and LVSVi (27.28  8.55 mL/m2 vs 37.42  5.35 mL/m2; p<0.001) compared to subjects who did not have post-operative LCOS (n=27). ROC analysis showed that the best AUC was found on LVEDVi (AUC 95.3%; 95% Confidence interval:90.6-100%). The best cut-off value for LVEDVi to predict the occurrence of LCOS after surgical closure of ASD was 53.3mL/m2 with sensitivity of 86.7% and specificity of 85.2%. Conclusion: This study showed that preoperative LVEDVi could predict LCOS after surgical closure of ASD with small-sized LV with a well-defined cut-off. The best cut-off value of LVEDVi to predict the occurrence of LCOS after surgical ASD closure was 53.5 mL/m2.